Psychoemotional correlates of prolonged grief in conditions of war trauma: a clinical and psychological analysis - Chaban, Oleg; Khaustova, Olena; Skrynnyk, Olga; Leshchuk, Iryna; Zelenko, Yelyzaveta (Psychosomatic Medicine and General Practice, 2025)
The full-scale war in Ukraine has caused a deep psychosocial resonance, resulting in a sharp increase in cases of mental disorders associated with the loss of loved ones. Prolonged grief disorder (PGD) is one of the most severe forms of reaction to loss, characterized by chronic separation distress, affective instability, and adaptation difficulties. Studying the psychoemotional characteristics of such patients allows us to better understand the mechanisms of transformation of an acute loss reaction into a pathological state.